(untitled) (The Review of Diabetic Studies, 2016)
BACKGROUND: Prediabetes has been related to an increased risk of developing diabetes and cardiovascular disease (CVD). AIM: The aim of the present study was to examine the effect of the Mediterranean diet on diabetes and CVD risk in subjects with impaired fasting glucose (IFG, i.e. fasting plasma glucose 100-125 mg/dl). METHODS: During 2001-2002, 3042 men and women (>18y) were enrolled for the study. The participants showed no clinical evidence of CVD or any other chronic disease, and were living in the greater Athens (Greece) area. In 2011 and 2012, the 10-year follow-up examinations were performed, including a working sample of n = 1875 participants without diabetes at baseline. Adherence to the Mediterranean diet at baseline evaluation was assessed using the MedDietScore (range 0-55). RESULTS: The prediabetic subjects (n = 343) had a significantly higher incidence of diabetes (25% vs. 10%, p < 0.001) and CVD (17.8% vs. 12.3%, p = 0.007) compared with subjects with normal glucose values. A significant trend towards lower diabetes and CVD incidence was observed with medium and high adherence to the Mediterranean diet compared with low adherence (p < 0.001). High adherence to the Mediterranean diet (>35/55 score) was associated with lower 10-year incidence of diabetes and CVD. In multiple logistic regression models, participants with high levels of adherence to the Mediterranean diet were significantly less affected by diabetes and CVD than those with low adherence levels. CONCLUSION: High adherence to the Mediterranean diet is associated with a low risk of developing diabetes and CVD in prediabetic subjects.